(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2019)
Daily life events concerning the state of the matter were found prone to alternative conceptions, it is essential to identify learning difficulties and remediate learners’ understanding mistakes. By categorizing students’ model of understanding, the part of understanding that should be remediated can be elucidated. This study focused on uncovering high school students’ model of understanding regarding the state of matter changes with forty 10th grade students as sample. Results suggested that only a small portion of the sample have an optimum model of understanding in which most students only have a theoretical or even inappropriate model of understanding.